Ketahanan Keluarga Long Distance Relationship dan Relevansinya terhadap Pembangunan Hukum Keluarga di Indonesia - Rismayanti, Tiara; Aris Setiyanto, Danu; Auzai, Muhammad (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
Long-Distance Relationships (LDR) families have more complex challenges than families living under one roof (proximal romantic relationships). Interestingly, some LDR families in Ngawi, Indonesia, can maintain their family relationships to be harmonious. This article explores the strategies used by the LDR family in realizing a harmonious family and its relevance in the development of Islamic family law in Indonesia. This article focuses on the six LDR families in Ngawi and analyzes them using psychological approaches and family resilience theory. Using case study research, the authors found that LDR families have six strategies to realize harmony in their families. Commitment strategies, effective communication, inner comfort, economic fulfillment, spiritual improvement, and mutual understanding to realize harmony in their families. The psychological approach used to understand couples indicates an emotional connection in the family. Thus, the authors argue that the construction of family law needs to focus on aspects of psychology that are associated with aspects of economics and communication. The first aspect fulfills the right of birth in the family, while the latter fulfills the inner right of the mother. Both aspects are essential to the LDR family and require balance.